The ethnic avant-garde : minority cultures and world revolution - Lee, Steven S. (Steven Sunwoo), 1978- (Modernist latitudes., 2015)
During the 1920s and 1930s, American minority artists and writers collaborated extensively with the Soviet avant-garde, seeking to build a revolutionary society that would end racial discrimination and advance progressive art. Making what Claude McKay called ;the magic pilgrimage" to the Soviet Union, these intellectuals placed themselves at the forefront of modernism, using radical cultural and political experiments to reimagine identity and decenter the West. Shining rare light on these efforts, The Ethnic Avant-Garde makes a unique contribution to interwar literary, political, and art histo